Tooth pulpitis (Texas Journal of Medical Science, 2021)
Pulpitis is an inflammatory process in the pulp (neurovascular bundle) and root canals of the tooth. The dental crown contains a cavity pulp chamber, where the plexus of blood vessels, connective tissue and nerve endings is located. All this together makes up the pulp, the main function of which is to nourish the coronal and root parts. The following article looks into the tooth pulpitis, its forms and symptoms.